Tetraphenylethylene derivative capped CH3NH3PbBr3 nanocrystals: AIE-activated assembly into superstructures. (29th November 2016) - Zhang, Feng; Zhou, Tianye; Liu, Guogang; Shi, Jianbing; Zhong, Haizheng; Dong, Yuping
Abstract : The surfaces of semiconductor nanocrystals have been known to be a very important factor in determining their optical properties. The introduction of functionalized ligands can further enhance the interactions between nanocrystals, which is beneficial for the assembly of nanocrystals. In a previous report, we developed a ligand-assisted reprecipitation method to fabricate organometal halide perovskite nanocrystals capped with octylamine and oleic acid. Here, a TPE derivative 3-(4-(1, 2, 2-triphenylvinyl)phenoxy)propan-1-amine, which shows a typical aggregation induced emission feature, is applied to replace octylamine to fabricate CH3 NH3 PbBr3 nanocrystals. The obtained CH3 NH3 PbBr3 nanocrystals were nanocubes (average diameter ∼ 11.1 nm) and are likely to assemble into ordered superstructures. By adjusting the chain length of the TPE derivative, we found that the assembly of the CH3 NH3 PbBr3 nanocrystals was correlated with the interactions between the TPE groups. This provides a new platform to investigate the ligand effects in nanocrystal solids and may potentially achieve enhanced optical and electrical properties.